Oscillatory neuronal activity patterns in Parkinson’s disease - Wichmann, Thomas (Henry Stewart Talks, 2014)
Basic anatomical functional facts in Parkinson’s disease, Methods for studying oscillatory brain signals, Oscillatory activity patterns in individual brain areas, Circuit-wide oscillations, Cause(s) of oscillatory activity patterns and the link to Parkinsonism, Use of oscillatory activity to assist/control deep brain stimulation
Updated at 2022/01/07